Postpartum blood pressure self-management following hypertensive pregnancy: protocol of the Physician Optimised Post-partum Hypertension Treatment (POP-HT) trial. Issue 2 (23rd February 2022) - Kitt, Jamie; Frost, Annabelle; Mollison, Jill; Tucker, Katherine Louise; Suriano, Katie; Kenworthy, Yvonne; McCourt, Annabelle; Woodward, William; Tan, Cheryl; Lapidaire, Winok; Mills, Rebecca; Khan, Maryam; et al.
Abstract : Introduction: New-onset hypertension affects approximately 10% of pregnancies and is associated with a significant increase in risk of cardiovascular disease in later life, with blood pressure measured 6 weeks postpartum predictive of blood pressure 5–10 years later. A pilot trial has demonstrated that improved blood pressure control, achevied via self-management during the puerperium, was associated with lower blood pressure 3-4 years postpartum. Physician Optimised Post-partum Hypertension Treatment (POP-HT) will formally evaluate whether improved blood pressure control in the puerperium results in lower blood pressure at 6 months post partum, and improvements in cardiovascular and cerebrovascular phenotypes. Methods and analysis: POP-HT is an open-label, parallel arm, randomised controlled trial involving 200 women aged 18 years or over, with a diagnosis of pre-eclampsia or gestational hypertension, and requiring antihypertensive medication at discharge. Women are recruited by open recruitment and direct invitation around time of delivery and randomised 1:1 to, either an intervention comprising physician-optimised self-management of postpartum blood pressure or, usual care. Women in the intervention group upload blood pressure readings to a 'smartphone' app that provides algorithm-driven individualised medication-titration. Medication changes are approved by physicians, who review blood pressure readings remotely. Women in the control arm follow assessment and medication adjustment by their usual healthcare team. The primary outcome is 24-hour average ambulatory diastolic blood pressure at 6–9 months post partum. Secondary outcomes include: additional blood pressure parameters at baseline, week 1 and week 6; multimodal cardiovascular assessments (CMR and echocardiography); parameters derived from multiorgan MRI including brain and kidneys; peripheral macrovascular and microvascular measures; angiogenic profile measures taken from blood samples and levels of endothelial circulating and cellular biomarkers; and objective physical activity monitoring and exercise assessment. An additional 20 women will be recruited after a normotensive pregnancy as a comparator group for endothelial cellular biomarkers. Ethics and dissemination: IRAS PROJECT ID 273353. This trial has received a favourable opinion from the London—Surrey Research Ethics Committee and HRA (REC Reference 19/LO/1901). The investigator will ensure that this trial is conducted in accordance with the principles of the Declaration of Helsinki and follow good clinical practice guidelines. The investigators will be involved in reviewing drafts of the manuscripts, abstracts, press releases and any other publications arising from the study. Authors will acknowledge that the study was funded by the British Heart Foundation Clinical Research Training Fellowship (BHF Grant number FS/19/7/34148). Authorship will be determined in accordance with the ICMJE guidelines and other contributors will be acknowledged. Trial registration number: NCT04273854 .